2022
DOI: 10.1002/tox.23713
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mesenchymal stem cells repair hexavalent chromium‐induced testicular injury by regulating autophagy and ferroptosis mediated by the AKT/mTOR pathway in rats

Abstract: There is no ideal therapy for testicular damage induced by Cr(VI); however, bone marrow mesenchymal stem cells (BMSCs) transplantation may be a promising therapy. A Cr(VI) solution was administered to rats by intraperitoneal injection for 30 days, then BMSCs from donor rats were transplanted. Two weeks later, decreased activity and appetite, along with other pathological changes, were improved in the BMSCs group. The location of BMSCs in damaged testes was observed via laser confocal microscopy. Chromium conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…In cancer cells, ferroptosis is suppressed through activation of the PI3K/AKT/mTOR pathway [ 180 ]. Taken together, BMSCs repair Cr(VI)-damaged testes by attenuating ferroptosis and downregulating proteins associated with autophagy through the positive regulation of AKT and mTOR phosphorylation [ 165 ], this provides a potential therapeutic target for infertility caused by damage by Cr (VI) in the testis.…”
Section: Application Of Mscsmentioning
confidence: 99%
“…In cancer cells, ferroptosis is suppressed through activation of the PI3K/AKT/mTOR pathway [ 180 ]. Taken together, BMSCs repair Cr(VI)-damaged testes by attenuating ferroptosis and downregulating proteins associated with autophagy through the positive regulation of AKT and mTOR phosphorylation [ 165 ], this provides a potential therapeutic target for infertility caused by damage by Cr (VI) in the testis.…”
Section: Application Of Mscsmentioning
confidence: 99%
“…20 Previous research has shown that cadmium exposure triggers ferroptosis by interrupting iron homeostasis and redox equilibrium in renal tubular dysfunction. 53 Furthermore, arsenic exposure was found to generate ferroptosis by promoting iron overload in the context of pancreatic dysfunction, 54,55 thereby highlighting the participation of ferroptosis in heavy metal toxicity. According to current research, MeHg exposure affects redox homeostasis and accelerates lipid peroxidation in the body by binding to mercaptan and selenol.…”
Section: The Nrf2 Signaling Pathway Was Implicated In Mehg-induced Ak...mentioning
confidence: 99%
“… Factor/reagent Categories Mechanism Ref. Busulfan Drug Downregulated NRF2ˎGPX4 and FPN expression [ 70 ] Tripterygium wilfordii polyglycoside tablet Drug Inhibit NRF2/xCT/GPX4 axis and FPN espression [ 118 , 119 ] Ischemia-reperfusion Testicular torsion Downregulated NRF2ˎGPX4 and FPN expression [ 71 ] Scrotal hyperthermia High temperature exposure Increase ACSL4 expression [ 107 ] Smoking (nicotine) Habit Downregulated NRF2 and GPX4 expression [ 82 , 108 ] 2.5-micron particulate matter Environmental factor Depletion of GSH and reduce GPX4 expression [ 83 , 110 ] DEHP Environmental factor Increase TFR1 and HO1 expression Reduce GPX4 level [ 27 , 126 , 135 ] BisphenolA Environmental factor Downregulate NRF2/HO1 and xCT/GPX4 pathwayˎActivate ACSL4 expression and ROS accumulation [ 111 , 112 ] Arsenite Heavy mental Downregulate xCT/GPX4 pathwayˎInduce ROS release and increase iron levels [ 84 ] Cdmium Heavy mental Reduce FTHˎFPN and xCT expressionˎDownregulate NRF2/HO1 pathway and enhance lipid peroxidation [ 69 , 115 ] Hexavalent chromium Heavy mental Inhibit xCT/GPX4 and mTOR [ 99 ] Co...…”
Section: The Role Of Ferroptosis In the Testismentioning
confidence: 99%
“…In a zinc-induced porcine model of testicular dysfunction, zinc induces ferroptosis by regulating mitochondrial autophagy [ 98 ]. Hexavalent chromium also causes testicular autophagy and ferroptosis in rats [ 99 ]. In addition, classical ferroptosis activators (such as ML-210) or inhibitors (such as ferrostatin-1, Fer-1) modulate intracellular autophagic flux in testicular injury.…”
Section: Ferroptosis-related Biological Responses In Testicular Injurymentioning
confidence: 99%